Bearing replacement extension without failure data. (1st January 2015) - Reuben, Lim Chi Keong; Corsar, Michael; Mba, David
For operators and maintainers, extension of maintenance intervals is desired to alleviate costs. For aircraft components, traditional failure time–based reliability methods can seldom be applied as defect occurrence tends to be rare. In this paper, methods to estimate the reduction in bearing reliability from extensions without failure data are explored. The methods are illustrated using a case study to extend a gearbox bearing replacement interval from 2, 000 to 3, 000 hours. Reliability assessment using the Weibull plot equation is first carried out. This assessment is then improved upon by using Monte Carlo simulation to estimate the variation in the bearing minimum life and to build confidence bounds. The assessment further takes into consideration usage severity by using flight monitoring data. A different approach using probabilistic modelling of damage accumulation is then applied. From this study, a conservative estimate of the bearing reliability from interval extension can be obtained.